Fenomena Kotak Kosong dalam Pemilukada Serta Implikasinya dalam Sistem Ketatanegaraan Indonesia - Ahmad Gelora Mahardika (Jurnal Adhyasta Pemilu, 2018)
The decision of Indonesian Constitutional Court No. 100/PUU-XII/2015 legitimizing single candidate give solution for democracy deadlock in some regions.Based on that decision, The Election Commission make a regulation giving alternative for some regions having only one candidate for choosing the picture of candidate against empty box.These battle in the beginning seems not fair because of political intention, empty box has no resources to compete with candidate. But, in the local election 2018, in some regions, empty box success to gain more voters than his rival. Winning of empty box in contestation of democracy became a proof that people feel tired because the system of regeneration in political parties not running well, other proof that single candidate that bring up by all political parties not always supported by voters. In the Indonesia constitutional law, the phenomenon of empty box surely implicate tomany problems. This writing will try to see this phenomenon and its implication according to Indonesian constitutional law.